Women, the Pandemic, and Humanitarian Solidarity (A Study of Fatayat NU’s Advocacy for Covid-19–Affected Communities in the Special Region of Yogyakarta) - Zunly Nadia (Lakpesdam PCNU Kota Salatiga, 2025)
The Covid-19 pandemic and social restriction policies (PSBB/PPKM) have reshaped everyday life and generated wide-ranging socio-economic impacts. Women have experienced layered vulnerabilities from increased unpaid care work and loss of livelihoods to rising domestic violence and heightened family precarity. Against this backdrop, this article poses two questions: (1) how did Fatayat NU DIY’s advocacy strategies build humanitarian solidarity for communities affected by Covid-19 in the Special Region of Yogyakarta; and (2) what were the impacts of this advocacy particularly for women and what enabling and constraining factors shaped its implementation? This study adopts a qualitative approach using a case-study design focused on PW Fatayat NU DIY, drawing on interviews with organizational leaders and volunteers, analysis of organizational documents and program records, and observations of advocacy practices during the pandemic. The findings show that Fatayat NU DIY implemented advocacy through a combination of emergency response and recovery initiatives: distribution of basic necessities, support for healthcare workers, assistance for pesantren clusters, public communication to prevent and counter misinformation, corpse care volunteers and vaccination support through GARFA, and recovery programs such as support for self-isolating patients, MSME assistance, family and domestic-violence consultation services through LKP3A, parenting programs, trauma healing, and food security initiatives. These efforts strengthened social protection and the resilience of women’s communities, although they were constrained by mobility restrictions, pervasive hoaxes and public resistance, and household economic pressures. The study recommends strengthening vulnerability mapping and beneficiary databases, developing crisis-response SOPs, expanding referral networks for women’s protection services, intensifying anti-misinformation digital literacy, and sustaining economic recovery programs through simple monitoring and evaluation mechanisms.